2019
DOI: 10.1021/acsami.9b15233
|View full text |Cite
|
Sign up to set email alerts
|

Oligomer Electrolytes for Light-Emitting Electrochemical Cells: Influence of the End Groups on Ion Coordination, Ion Binding, and Turn-on Kinetics

Abstract: The electrolyte is an essential constituent of the light-emitting electrochemical cell (LEC), since its operating mechanism is dependent on the redistribution of mobile ions in the active layer. Recent developments of new ion transporters have yielded high-performance devices, but knowledge about the interactions between the ionic species and the ion transporters and the influence of these interactions on the LEC performance is lacking. We therefore present a combined computational and experimental effort that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…[ 15a,b ] Thus, a plausible explanation for the observed mobility behavior is that the anion mobility is essentially the same in both LECs, whereas the cation mobility is higher with the smaller TMPE‐OH ion transporter than the larger TMPE‐OC. However, we emphasize that other factors, such as the active‐material morphology, [ 15a,22 ] the initial spatial distribution of the electrolyte, [ 21a ] and the release kinetics of cations from the electrolyte complex, [ 23 ] also can influence the effective ion mobility. In the morphology context, we mention that an AFM study revealed that the active materials featured a very smooth surface morphology, regardless of the ion‐transporter selection (see Figure S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 15a,b ] Thus, a plausible explanation for the observed mobility behavior is that the anion mobility is essentially the same in both LECs, whereas the cation mobility is higher with the smaller TMPE‐OH ion transporter than the larger TMPE‐OC. However, we emphasize that other factors, such as the active‐material morphology, [ 15a,22 ] the initial spatial distribution of the electrolyte, [ 21a ] and the release kinetics of cations from the electrolyte complex, [ 23 ] also can influence the effective ion mobility. In the morphology context, we mention that an AFM study revealed that the active materials featured a very smooth surface morphology, regardless of the ion‐transporter selection (see Figure S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…As seen in Figure , addition of PEO gives a much stronger shift response than for any of the carbonyl-coordinating polymers, indicating its much stronger interactions with the Li + ions. PEO is known to strongly coordinate the lithium through chelating structures created from its ether oxygen atoms, whereas the coordination structures formed from the carbonyl oxygens in the polyester and polycarbonate electrolytes result in a much weaker coordination. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…Yet another property that may affect the coordination structure and ion pairing in the polymer electrolyte system is the dielectric constant. Previously, a correlation between coordination strength and ion pairing has been observed, 44 but its interrelation with the dielectric constant remains unclear. The resulting ion paring should, however, not significantly affect the transference number, unless the ion clustering results in an extensive formation of ion triplets.…”
Section: Resultsmentioning
confidence: 99%